2023
DOI: 10.3390/rs15030836
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Scattering and Doppler Spectrum Simulation of Land–Sea Junction Composite Rough Surface

Abstract: In this paper, a weighted arctangent function is used in conjunction with the spectral method to generate a land–sea junction composite rough surface under the spatially homogeneous and time-stationary hypotheses. The exponential correlation function and the Joint North Sea Wave Project (JONSWAP) spectrum, combined with an experiment-verified shoaling coefficient, are applied to model the land surfaces and the time-varying sea surfaces separately. The second-order small slope approximation (SSA-II) with tapere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Paper [28] generated the rough surface based on the weighted tangent function and spectrum method to simulate the composite rough surface at the actual land-sea interface and applied a more accurate second-order small slope approximation (SSA-II) to calculate the electromagnetic scattering of the model. The Doppler spectra of this composite rough surface and the sea surface are compared, and it is found that the scattering coefficients of the land-sea composite rough surface are smaller than those of the sea surface under certain polarization modes.…”
Section: Literature Analysismentioning
confidence: 99%
“…Paper [28] generated the rough surface based on the weighted tangent function and spectrum method to simulate the composite rough surface at the actual land-sea interface and applied a more accurate second-order small slope approximation (SSA-II) to calculate the electromagnetic scattering of the model. The Doppler spectra of this composite rough surface and the sea surface are compared, and it is found that the scattering coefficients of the land-sea composite rough surface are smaller than those of the sea surface under certain polarization modes.…”
Section: Literature Analysismentioning
confidence: 99%